2000
DOI: 10.1002/1097-4636(200010)52:1<219::aid-jbm28>3.0.co;2-f
|View full text |Cite
|
Sign up to set email alerts
|

Modulating the biocompatibility of polymer surfaces with poly(ethylene glycol): Effect of fibronectin

Abstract: A novel approach described earlier for improving polymer substratum biocompatibility(1) is further elucidated. Polysulfone (PSf) spin-coating films were modified by covalent end-on grafting of hydrophilic and sterically demanding photo-reactive poly(ethylene glycol) (PEG) conjugates (ABMPEG; 10 kDa). The degree of grafting density was varied systematically, yielding a wide spectrum of attained surface characteristics monitored by air-water contact angles (captive bubble method). Fibronectin (FN) adsorption was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
63
0

Year Published

2001
2001
2015
2015

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 98 publications
(66 citation statements)
references
References 36 publications
3
63
0
Order By: Relevance
“…It is well documented that protein adsorption depends on the surface properties which produces great impact on the cellular interaction (Altankov et al, 2000;Keselowsky et al, 2003;Lan et al, 2005). Here we found that significantly increased Col IV adsorption on hydrophobic ODS does not support cellular interaction, a fact observed also for other matrix proteins (Grinnell and Feld, 1982;Tzoneva et al, 2002) and cell systems (Grinnell and Feld, 1982).…”
Section: Discussionsupporting
confidence: 50%
“…It is well documented that protein adsorption depends on the surface properties which produces great impact on the cellular interaction (Altankov et al, 2000;Keselowsky et al, 2003;Lan et al, 2005). Here we found that significantly increased Col IV adsorption on hydrophobic ODS does not support cellular interaction, a fact observed also for other matrix proteins (Grinnell and Feld, 1982;Tzoneva et al, 2002) and cell systems (Grinnell and Feld, 1982).…”
Section: Discussionsupporting
confidence: 50%
“…This is also applicable to the PEGT:PBT substrates synthesized and studied herein, and was examined using PEG length and weight ratio. Changes in substrate composition and wettability have been shown to influence Fn conformation 36 , with conformational interplay between competitively adsorbed Fn and albumin at the material-protein interface enhancing FN activity 37 . The amount of surface PEG in other polymers has been shown to inversely correlate with Fn coating and affects its conformation 38 .…”
Section: Discussionmentioning
confidence: 99%
“…Among other physical and chemical techniques to improve the surface biocompatibility [19][20][21][22], plasma surface modification is used to adapt the surface properties by functionalization of the material surface to control the biological response. Different functionalities have been investigated, such as carboxyl [23], hydroxyl [24] and primary amine [25] (see figure 2).…”
Section: Plasma Mediamentioning
confidence: 99%